Re-examining medical assistance in dying for mature minors in Canada: Reflections for health leaders. Issue 3 (May 2023) - Campbell, Sydney; Denburg, Avram; Moola, Fiona; Carnevale, Franco A.; Petch, Jeremy
In Canada, Medical Assistance in Dying (MAiD) is legal for many Canadians based on several criteria, though minors who are deemed sufficiently capable to make medical decisions (i.e. mature minors) remain ineligible. In this article, we provide insight into recent philosophical and legal evidence related to MAiD for mature minors. We begin by providing an overview of literature pertaining to MAiD for mature minors in particular (including evidence from Belgium and the Netherlands), followed by a discussion on the lessons that can be learnt from Canada's MAiD implementation process (in general) and other forms of paediatric end-of-life care. As a whole, we aim to highlight some key takeaway messages for health leaders to consider as deliberations on MAiD for mature minors continue.